Using INTERNET for Business - Barčkutė, Ona; Mikalauskienė, Audronė (Ekonomika, 1997)
Today, computer based information systems play a critical role in business operations. Information has become a very important and valuable resource for all kinds of businesses. Moving vast amounts of information quickly across great distances is one of the most pressing needs of today. Some businesses have discovered that their area of service naturally extends to a global scale. So, networking technology and the Internet is becoming an absolute necessity. The Internet with global networking technology involves people and organizations in similar work, where they can share and communicate new ideas for various aspects of business. The Internet has also become a cost-effective and quicker way to transfer documents. Although more organizations have access to the Internet, a great deal of problems still exist that deal with what the Internet is and what an organization needs to do in order to be successful with the Internet. This article deals with the issue of why the Internet is important for business and how it should be used to gain an advantage in business.